A SCIENTIFIC CAREER IN MEDICINE BEGINS IN STUDENT YEARS - Boymuradov, Sh.A.; Okhunov, A.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
In the context of modernization of the system of higher medical education in Uzbekistan, the formation of research motivation among students of medical universities is of particular relevance. The scientific activity of students at the early stages of training is not only a factor in deepening professional knowledge, but also the basis for sustainable personnel growth in the scientific and clinical fields. The article discusses the key aspects of the inclusion of students in research activities, analyzes the existing organizational forms - from student scientific circles to participation in scientific conferences and competitions. It is shown that the formation of scientific thinking and research competence in student years is an important link in the training of future doctoral students (PhD) and researchers. The main difficulties faced by young researchers are outlined, and ways to integrate the scientific component into the educational process are proposed. The need for institutional support for young people at all stages of the scientific trajectory, from students to doctoral studies, is emphasized.